Kombinasi Metode AHP dan EDAS dalam Penilaian Kinerja Dosen di Perguruan Tinggi - Yuan Sa’adati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Faculty performance evaluation is a process within an organization aimed at assessing and improving the performance of lecturers. Regular performance evaluations are essential for enhancing teaching quality and the professional development of faculty members. However, in practice, faculty performance evaluations are often still conducted manually, which may lead to human errors and delays in data processing, thereby affecting the timeliness of decision-making. Decision Support Systems (DSS) are introduced to assist in decision-making, particularly when there is uncertainty regarding the best approach to make a decision. This study adopts a combined methodology, using the Analytical Hierarchy Process (AHP) for criterion weighting and Evaluation based on Distance from Average Solution (EDAS) for ranking. The use of DSS aims to streamline the evaluation process while minimizing potential errors. The evaluation is based on six criteria: student evaluation, peer evaluation, education, research, community service, and participation in seminars or guest lecturing activities. The results consistently identify alternative A3 as the best option, with a score of 0.312 in the faculty performance evaluation.